2017
DOI: 10.26510/2394-0859.pbe.2017.31
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial contamination of toilets and bathroom doors handle/knobs at Daeyang Luke hospital

Abstract: Objective: The aim of the study was to determine the level of bacterial contamination of door handles/knobs of toilets and bathrooms at Daeyang Luke Hospital.Methods: Fomite can be described as a non-living object capable of carrying infectious organism and it is considered as one of the major source of spread of hospital acquired infection. In this study, door handles/knobs were swabbed with sterile swab stick moistened with sterile water. The content was evenly transferred to nutrient agar petric dish and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 7 publications
3
22
1
Order By: Relevance
“…This observation may be as a result of the number of students that use a particular toilet in the University studied. This is similar to the work of [16]. The researcher observed that the toilets at Daeyang Luke Hospital which had more users were more contaminated than other bathrooms with less users.…”
Section: Enumeration Of Bacteria Isolated From Toilet Seatssupporting
confidence: 77%
“…This observation may be as a result of the number of students that use a particular toilet in the University studied. This is similar to the work of [16]. The researcher observed that the toilets at Daeyang Luke Hospital which had more users were more contaminated than other bathrooms with less users.…”
Section: Enumeration Of Bacteria Isolated From Toilet Seatssupporting
confidence: 77%
“…Osteomyelitis caused by C. koseri is very rare, and there have been very few cases of documented musculoskeletal infections in humans 4. Of the reported cases of musculoskeletal infections involving C. koseri, newborns and elderly persons are at the highest risk of infection 4. Diabetes was associated with all three cases of C. koseri osteomyelitis infections involving the foot with peripheral vascular disease being present in two 4–6.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomyelitis caused by C. koseri is very rare, and there have been very few cases of documented musculoskeletal infections in humans 4. Of the reported cases of musculoskeletal infections involving C. koseri, newborns and elderly persons are at the highest risk of infection 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of bacteriological assessment of door handles/knobs of toilets and washrooms was conducted by Frank Ngonda in a hospital setting in 2017,[ 15 ] which revealed some bacteriological similar results. Among the total of 442 samples, 184 cases (41.6%) were contaminated and also S. aureus was the most bacteria had isolated.…”
Section: Discussionmentioning
confidence: 99%